(3fXe GdLhGgQ (B( (3aj GdCdaGX GdcJGHjI (B)s - (3CHh SYjOs
(3ChdgG (B:s
(3GdYRI ddg hMOg, hGdMeO ddg MeO GdTGcQjf , hHYO aEfi bQCJ YOI cJH eUfaI ai GdCdaGX GdcJGHjI , hhLOJgG ZjQ eSJbUGI ai eYGfjgG hdG eSJhaGg hUQaJ gei Edi JUfja cJGH ajgG jSJZfi s
(3BNQgG (B:s
(3hUQUQI GdHGRi hJZQjO GdMeGe hVLjL Gdbhe hYLJge Je cJGH fXe GdLhGgQ s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQGJ GdCUd (B:s
(3GdfSNI eYGQVI Ydi fSNI GdeDpqdas
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdLGeY GdcHjQ HUfYGA (B((3GddZI GdYQHjI (B37) s
Keywords: (3GddZIs